GAMBARAN KARAKTERISTIK DAN TINGKAT PENGETAHUAN IBU NIFAS TENTANG MANFAAT ASI DAN METODE AMENOREA LAKTASI (MAL) DI PRAKTIK MANDIRI BIDAN (PMB) NY. MASRIAH KELURAHAN KEJAMBON KECAMATAN TEGAL TIMUR KOTA TEGAL - Dewi Elliana; Sri Mularsih (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Coverage of exclusive breastfeeding to babies aged 6 months in Tegal City is still below the target, namely 65.9% of the target of 80%. that most of the people of Tegal City do not know the benefits of breast milk and do not recognize that exclusive breast milk is the best food for babies and one of the natural birth control methods (Lactational Amenorrhea Method or MAL). The type of research is descriptive and the nature of the research is a survey with a saturated sampling technique with a total of 43 respondents. The research results showed that 16 (37.2%) respondents were aged more than 30 years, 14 (32.6%) respondents were aged between 26 - 30 years and 30.2% (13 respondents) were aged less than 25 years. Respondents with primary education levels were 24 (55.8%) respondents, secondary education levels were 32.6% (14 respondents), and higher education levels were 11.6% (5 respondents). There were 21 (48.8%) respondents who did not work, 32.6% (14 respondents) private sector workers, and 18.6% (8 respondents) as workers, traders, civil servants and entrepreneurs. Respondents with knowledge about the benefits of good breast milk were 19 (44.2%) respondents, 18.6% (8 respondents) had enough, and 37.2% (16 respondents) had less. Respondents with knowledge about MAL were in the poor category as many as 21 (48.8%) respondents, 39.5% (17 respondents) enough and 11.6% (5 respondents) good.